2013
DOI: 10.1007/s10238-013-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant effect of the Malaysian Gelam honey on pancreatic hamster cells cultured under hyperglycemic conditions

Abstract: Type 2 diabetes consists of progressive hyperglycemia, insulin resistance, and pancreatic β-cell failure which could result from glucose toxicity, inflammatory cytokines, and oxidative stress. In the present study, we investigate the effect of pretreatment with Gelam honey (Melaleuca spp.) and the individual flavonoid components chrysin, luteolin, and quercetin, on the production of reactive oxygen species (ROS), cell viability, lipid peroxidation, and insulin content in hamster pancreatic cells (HIT-T15 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…It indicated that GH decreases the damages caused by increased free radicals production in hyperglycaemic state. Moreover, the study also showed that pre-treatment with GH exhibited a significant increase (p < 0.05) in insulin content (Batumalaie et al 2013). From the above findings, it was proven that GH has both antioxidant and anti-diabetic properties as it increased the insulin content in hyperglycaemic state.…”
Section: Antioxidant Properties Of Ghmentioning
confidence: 73%
“…It indicated that GH decreases the damages caused by increased free radicals production in hyperglycaemic state. Moreover, the study also showed that pre-treatment with GH exhibited a significant increase (p < 0.05) in insulin content (Batumalaie et al 2013). From the above findings, it was proven that GH has both antioxidant and anti-diabetic properties as it increased the insulin content in hyperglycaemic state.…”
Section: Antioxidant Properties Of Ghmentioning
confidence: 73%
“…A study investigated the effect of pre-treatment with Gelam honey, and the individual flavonoid components chrysin, luteolin, and quercetin on the production of reactive oxygen species, cell viability, lipid peroxidation, and insulin in hamster pancreatic cells, cultured under normal conditions and hyperglycemic, the pre-treatment of cells with Gelam honey extract or flavonoid components showed a significant decrease in the production of reactive oxygen species, glucose-induced lipid peroxidation, and a significant increase in insulin content and viability of cultured cells under hyperglycemic conditions. The results indicated the in vitro antioxidant property of Gelam honey and flavonoids on hamster β cells, creating a protective effect against hyperglycemia [80]. Another study demonstrated the effect of honey on diabetics, the study with rats concluded that the pancreatic tissues of rats with diabetes were exposed to great oxidative stress and that supplementation with other honey, Tualang honey, had protective effects in the pancreas [80,82].…”
Section: Antioxidantsmentioning
confidence: 96%
“…The results indicated the in vitro antioxidant property of Gelam honey and flavonoids on hamster β cells, creating a protective effect against hyperglycemia [80]. Another study demonstrated the effect of honey on diabetics, the study with rats concluded that the pancreatic tissues of rats with diabetes were exposed to great oxidative stress and that supplementation with other honey, Tualang honey, had protective effects in the pancreas [80,82].…”
Section: Antioxidantsmentioning
confidence: 96%
See 1 more Smart Citation
“…It also induces GLUT-4 translocation in 3T3-L1 adipocyte cells, suggesting an increase of glucose uptake into those cells [28]. Several studies showed that chrysin has hypoglycemic effects on diabetic mice [29,30]. Pancreatic beta cells, the function of which is important to prevent diabetes mellitus, are protected by the antioxidant activity of chrysin [31].…”
Section: Effect On Diabetesmentioning
confidence: 99%